Taxonomic notes on the Chamaecladon clade of Homalomena (Araceae) in Tapanuli, Sumatera, with the description of a new species - Yudistira, Yuda R.; Hase, Keisuke; Weessies, Nils (Phytotaxa, 2026)
A new species of Homalomena [Chamaecladon clade] (Araceae), Homalomena rex Weessies, K.Hase & Yudistira, is described and illustrated from lowland forest of North Sumatera, Indonesia. H. rex is distinguished by its large plicate leaf blades with strongly recurved margins and by a prominently stipitate spadix, a combination of characters not observed in allied Sumatran taxa. Notes on its morphology, ecology, and conservation status are provided.